Estudo de associação dos SNPS nos genes: MUC1, COX-2 E TNF-Α e a susceptibilidade ao desenvolvimento da carcinogênese mamária em mulheres no Estado da Paraíba - Araújo, Maria Isabela Ferreira de (2019)
Breast cancer (CM) is considered a multifactorial neoplasm, related to genetic, epigenetic and environmental factors. The presence of single nucleotide polymorphism (PNS) contributes to the risk of developing diseases, including breast carcinoma. The purpose of this study was to genotyping SNPs in the MUC-1 (rs4072037), COX-2 (rs533479217) and TNF-α (rs1800629) genes in 100 paraffin tissue samples from patients with histopathological diagnosis of CM. The results were obtained by the Dideoxy Unique Allele Specific - PCR (DSASP) method. All SNPs studied suggested a possible association with susceptibility to CM development. The R statistical tool (R Core Team, 2016) was used for statistical analysis and application of Chi-square and Fisher's Exact test. SNPs rs4072037, rs533479217 and rs1800629 showed a significant association with CM in the analyzed samples (p˂0.005). The results suggest a possible association of MUC-1, COX-2 and TNF-α SNPs with susceptibility to CM development and may be considered possible molecular markers of CM.